Influence of Asian-Pacific Oscillation on Precipitation in Central Eastern China during Autumn (1960–2016) - Zouxing Lin; Jiajin Zhu; Wei Hua; Guangzhou Fan (Advances in Meteorology)
The Asian-Pacific Oscillation (APO) plays an important role in precipitation in Central Eastern China (CEC). This study analyzed observational and reanalysis data to investigate CEC precipitation during autumn (1960–2016) and its association with the APO. The APO index (APOI) was redefined, and an autumn CEC precipitation index (CECPI) was calculated to elucidate the relationship between the APO and CEC precipitation. Significant positive correlation (correlation coefficient: 0.60) was found between the APOI and CECPI. Further analysis revealed anomalous southerly winds at 850 hPa over CEC when the APO was strong, which corresponded to anomalous strengthened (weakened) sea level pressure and increased 500-hPa geopotential height over Asia (the Pacific), together with strong meridional shear of the East Asian jet. This configuration is conducive to transportation of warm moist air to CEC during strong APOI years (SAY), but the effect is much diminished during weak APOI years. Moreover, strengthening of both the Walker Circulation of the tropical Pacific and the anomalous upward movement (and convergence) over the Western Pacific (WP) observed during SAY is also conducive to the formation of precipitation in CEC. A possible physical explanation for the close association of the APO with tropical circulation changes is that decreased (increased) sea surface temperature in the tropical eastern Pacific (WP and extratropical Pacific) is beneficial for stimulating a strong APO teleconnection pattern, which further affects precipitation in CEC by strengthening the connection between tropical and subtropical regions.